Algebraic thinking profile of prospective mathematics teacher students with medium mathematics ability according to solo taxonomy - Rochana, Siti; Wahyuniar, Lilia Sinta; Shofia, Niska; Mahdiyah, Umi (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2020)
This study aims to describe the algebraic thinking profile of prospective mathematics teacher students according to the SOLO taxonomy. The research was conducted at the Nusantara University PGRI Kediri. The research subjects were students who are prospective mathematics teachers with moderate or average abilities. Subjects are selected based on course scores and information from several lecturers who are teaching the subject. Besides that, the willingness and openness of the subject is also a consideration for choosing this subject. The instrument used in this study was a matter of algebraic problems. The method used is a qualitative method which refers to the written test and interview. The questions that are done consist of tests of algebra problems for pattern components and algebra problem tests for variable components. The results showed that students of prospective mathematics teachers with moderate mathematical abilities met the indicators of algebraic thinking, namely being able to find certain terms in a given pattern but were unable to generalize the given pattern and could not understand variables as general form numbers in algebraic form.